1977
DOI: 10.2172/7211874
|View full text |Cite
|
Sign up to set email alerts
|

Radiological impact of airborne effluents of coal-fired and nuclear power plants

Abstract: 1. Introduction 2 2. Natural Radioactivity in Coal 3 3. Source Term for a Model Advanced lOOO-MW(e) Coal-Fired Power Plant 8 k. Source Terns for Model Advanced Nuclear Plants 10 5. Dose Calculations U 5.1 Source Tenr. Methodology 16 6. Results and Discussion 17 6.1 Percentage Contributions of Radionuclides to Exposure and Exposure Pathways 20 6.2 The Effect of Varying Food Intakes on Dose Commitments 28 6.3 Effect of Higher Uranium and Thorium Concentrations on Dose Commitments 29 6. If The Effect of Higher Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Because the wind was from the northwest 50% of the sampling time, it would-be expected that if the stack emissions were significant the maximum radionuclide concentration would be observed at the south- (1) radon-222 is in secular equilibrium with uranium-234 in coal, and .. McBride et al [36] have suggested that, ..…”
Section: Radionuclide Balance For the Power Plant"mentioning
confidence: 99%
“…Because the wind was from the northwest 50% of the sampling time, it would-be expected that if the stack emissions were significant the maximum radionuclide concentration would be observed at the south- (1) radon-222 is in secular equilibrium with uranium-234 in coal, and .. McBride et al [36] have suggested that, ..…”
Section: Radionuclide Balance For the Power Plant"mentioning
confidence: 99%
“…The EIA report, produced by a private Turkish company so called Dokay [1], and approved by Turkish government on December 2014, which includes the amount of annual radioactive release shown in section V. indicates that annual air-born releases from a 1,000 MWe PWR is about 13.935 Curie, 1,100 curies of which is tritium, mostly in gas form [5].…”
Section: Misrepresentation Of or Failure To Itemize And Specify The Rmentioning
confidence: 99%
“…and other animals through inhalation and plants through fumigation while those entering the aquatic and terrestrial environments reach plants and animals through root uptake and ingestion. Trace elements and radionuclides in U.S. coals have been widely studied (4,7,8). Concentrations of trace elements in coal are sometimes difficult to determine accurately and tend to vary considerably among different coal types (Table 1).…”
Section: <10mentioning
confidence: 99%
“…Numerous reports have been prepared in recent years concerning these effects relative to our current pattern of coal utilization of approximately 650 million tons per year. Most studies have dealt with specific parameters of coal utilization such as health effects of coal combustion (1), toxicity of coal-derived trace elements (2), effects of coal-derived trace elements on water quality (3), and effects of coal-derived radionuclides (4). Recently several reports have appeared addressing an integrated assessment of coal utilization (5-8) and these reports have been utilized extensively in developing the following materials.…”
Section: Introductionmentioning
confidence: 99%